2006
DOI: 10.1086/500936
|View full text |Cite
|
Sign up to set email alerts
|

Influx of Extended-Spectrum  -Lactamase--Producing Enterobacteriaceae into the Hospital

Abstract: We report high rates of bacteremia and colonization with ESBL-producing Enterobacteriaceae at admission to our institution, which may undermine infection-control measures and complicate the selection of empirical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
220
4
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(254 citation statements)
references
References 42 publications
16
220
4
9
Order By: Relevance
“…42,51 In these institutions antibiotic resistance is a growing problem and outbreaks of infection with multidrug resistant organisms (MDROs) are frequently reported. 6,42 Long-term care facilities may play an important role in the spread of resistant organisms, including Klebsiella pneumonia carbapenemase (KPC)-producing Enterobacteriaceae, 52 extended spectrum b-lactamase (ESBL) producing organisms, 53 metallo-b-lactamase (MBL) producing, 54 MRSA, 55 VRE and MDR Acinetobacter baumanii. 56 March et al found that among LTCF residents in 2012, 54% were colonized with 1 resistant organism.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…42,51 In these institutions antibiotic resistance is a growing problem and outbreaks of infection with multidrug resistant organisms (MDROs) are frequently reported. 6,42 Long-term care facilities may play an important role in the spread of resistant organisms, including Klebsiella pneumonia carbapenemase (KPC)-producing Enterobacteriaceae, 52 extended spectrum b-lactamase (ESBL) producing organisms, 53 metallo-b-lactamase (MBL) producing, 54 MRSA, 55 VRE and MDR Acinetobacter baumanii. 56 March et al found that among LTCF residents in 2012, 54% were colonized with 1 resistant organism.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Une étude israélienne récente a mis en évidence que 13,7 % des souches d'entérobactéries isolées d'hémocultures pré-levées au moment de l'admission des patients à l'hôpital possédaient une -lactamase à spectre élargi. De même, 10,8 % des 241 patients dépistés étaient porteurs de EBLSE [14]. Plus récemment, une étude réalisée en Arabie saoudite [15] à partir de coprocultures a identifé un taux de portage d'EBLSE de 13,5 % chez les sujets sains et de 26,1 % chez les sujets hospitalisés.…”
Section: Microbiologieunclassified
“…2 We mentioned the factors that might increase the risk of irritation of oral mucosa and warned the healthcare workers who wanted to implement this intervention for their patients. However, we considered that the benefit of VAP prevention outweighed the risk of adverse effects.…”
mentioning
confidence: 99%
“…Data from Israel and Saudi Arabia indicate colonization rates in excess of 10% and even 26%. 2,3 Rectal colonization is a known risk factor for infection due to ESBL-producing Enterobacteriaceae. 2 Reddy et al 1 reported that 35 (8.5%) of 413 patients colonized with ESBLproducing Enterobacteriaceae developed a subsequent bloodstream infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation